Racism, Empiricism and Criminal justice (Canada : The Collective Press, 1990)
This book advanced the idea of preparing a reader on the subject of discrimination in the American Criminal Justice . The project was unanimously endorsed, and the contents of the following pages represents the product of a collective effort from variety of individuals.
Section 1. Debates -- section 2. Racism, Empiricism and Policy Implications -- Section 3. Synthesis .
Includes bibliographical references.
Keywords: DISCRIMINATION